Q&A - Ask Doubts and Get Answers
Q

Simplify each of the following expressions: (iv)

2.  Simplify each of the following expressions:

(iv)     \left (\sqrt{5}-\sqrt{2} \right )\left ( \sqrt{5}+\sqrt{2} \right )

Answers (1)
Views

Given number is  \left (\sqrt{5}-\sqrt{2} \right )\left ( \sqrt{5}+\sqrt{2} \right )

Now, we will reduce it into
\Rightarrow \left (\sqrt{5}-\sqrt{2} \right )\left ( \sqrt{5}+\sqrt{2} \right )= \left ( (\sqrt{5})^2-(\sqrt{2})^2 \right )           \left ( using \ (a+b)(a-b)=a^2-b^2\right )
                                                           =5-2
                                                           =3

Therefore, the answer is  3.

Exams
Articles
Questions